A three-dimensional hyaluronic acid-based niche enhances the therapeutic efficacy of human natural killer cell-based cancer immunotherapy. (July 2020) - Ahn, Young Ha; Ren, Long; Kim, Seok Min; Seo, Sang-Hwan; Jung, Cho-Rok; Kim, Da Seul; Noh, Ji-Yoon; Lee, Soo Yun; Lee, Hyunseung; Cho, Mi Young; Jung, Haiyoung; Yoon, Suk Ran; et al.
Abstract: Adoptive transfer of natural killer (NK) cells is becoming one of the most important parts of cancer immunotherapy. However, recent accomplishments have focused on the improvement of the targeting effects based on the engineering of chimeric antigen receptors (CARs) on cell surfaces. Despite the large quantity of therapeutic cells required for clinical applications, the technology for ex vivo expansion is not well developed. Herein, a three-dimensional (3D) engineered hyaluronic acid-based niche for cell expansion (3D-ENHANCE) is introduced. Compared with the conventional two-dimensional (2D) method, NK-92 cell lines and human EGFR-specific (CAR)–NK cells cultured in 3D-ENHANCE yield favorable mRNA expressions, elevated cytokine release, upregulated proliferative and tumor-lytic abilities, and result in enhanced antitumor efficacy. Furthermore, controllable degradation rates can be realized by tuning the formulation of 3D-ENHANCE so that it can be applied as an implantable cell reservoir at surgical sites. In vivo results with the incompletely resected MDA-MB-231 model confirm that the peri-operative implantation of 3D-ENHANCE prevents the relapse and metastases after surgery. Overall, 3D-ENHANCE presents an effective cytokine-free niche for ex vivo expansion and postsurgical treatment that enhances the low-therapeutic efficacy of human NK cells.